PRAKTIK SENI LUDRUK DI SURABAYA: STRATEGI KEBERTAHANAN SENI TRADISIONAL LUDRUK SURABAYA - JATMIKO, DHENY; PRASAJA, AGUNG (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
The study discusses the strategies used by ludruk groups as the survival strategies of Ludruk as a traditional form of art in Surabaya during the New Order. In Surabaya, there are at least three popular Ludruk groups: the groups of Ludruk RRI Surabaya, Cak Kartolo, and Irama Budaya. The success of Ludruk RRI Surabaya can be seen from their continuity and their success at socializing the government programs; the success of Kartolo is marked by 95 tapes which are well received; while the success of Irama Budaya is proven with the great number of audience (around 500) in 1998-2003. The analysis method applied is Pierre Bourdieu’s genetic structuralism method. Based on the study, it is found that the strategies used by the ludruk groups in Surabaya are playing the role as the government’s art media, optimalizing dagelan (comedy), and giving space for the minority while maintaining convension. Keywords: Ludruk RRI Surabaya, Kartolo, Irama Budaya, Strategy